Eine andere Kirche ist notwendig - eine andere Kirche ist möglich: Oscar Romeros Ruf zu Umkehr und Hoffnung - Sobrino, Jon (Zeitschrift für katholische Theologie, 2010)
On the occasion of the 30th anniversary of his assassination Sobrino reflects on the life and death of Oscar Romero and their implications for a church that is always renewing itself.